Clinical Observation: Effect of a Second Transpositioned Variant in a Family with Autosomal Dominant Ryanodine Receptor-1–Related Disease - Avnon, Tomer; Svirsky, Ran; Orr-Urtreger, Avi; Sagie, Liora; Fattal-Valevski, Aviva; Fellig, Yakov; Ben-Shachar, Shay (Journal of Pediatric Genetics, 2020)
Mutations in the ryanodine receptor-1 (RYR1) may cause disorders inherited in an autosomal dominant/recessive fashion. Sequencing of RYR1 in an infant of Ashkenazi Jewish descent with severe hypotonia, dislocation of hip, torticollis and scoliosis, and paternal family history of autosomal dominant mild disease. The child was compound heterozygote for a missense variant c.7042G > A inherited from her father associated with autosomal dominant disease, and a missense variant of unknown significance c.5309C > T inherited from an asymptomatic mother. This case raises the possibility of a dominant disease complicated by a second variant in the other allele serving as a modifier.
Keywords: central core disease; malignant hyperthermia susceptibility; ryanodine receptor-1 gene